2012
DOI: 10.1074/jbc.m111.336370
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imprint of Enzyme Active Site by Camel Nanobodies

Abstract: Background:The generation of catalytic antibodies (abzymes) by the anti-idiotypic antibody approach was hampered by their incompatible CDR structure with the active site of the enzyme. Results: The high incidence of anti-idiotypic abzymes with alliinase activities was produced by the anti-idiotypic nanobody approach. Conclusion:The anti-idiotypic nanobodies are efficient natural enzyme mimics. Significance: This study provided a new approach for producing abzymes that could be broadly applied to antibody-catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Many reports about the unique property of camel antibody binding to the incompatible antigen, which differs from the conventional antibody, were published. A special class of antibodies in members of the Camelidae family that consist of only heavy chains was discovered (reviewed by Li et al 2012). Daley et al (2010) reported distinctions in the regulation and function between camelid heavy-chain isotypes on testing vaccinated alpacas for West Nile virus antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports about the unique property of camel antibody binding to the incompatible antigen, which differs from the conventional antibody, were published. A special class of antibodies in members of the Camelidae family that consist of only heavy chains was discovered (reviewed by Li et al 2012). Daley et al (2010) reported distinctions in the regulation and function between camelid heavy-chain isotypes on testing vaccinated alpacas for West Nile virus antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, abzyme A17, having a deep antigen‐binding pocket, was found to be an interesting antidote for the detoxification of organophosphorus warfare agents . Abzymes can also be used as enzyme substitutes in antibody‐directed enzyme prodrug therapy against cancer . Antibody‐directed enzyme prodrug therapy involves the use of antibody–enzyme conjugates to leverage the target binding and catalytic functions of both constituents.…”
Section: Enzyme Mimics and Their Applicationsmentioning
confidence: 99%
“…[217] Abzymes can also be used as enzymes ubstitutes in antibody-directed enzyme prodrug therapy against cancer. [218,219] Antibody-directed enzymep rodrug therapy involves the use of antibodyenzyme conjugatest ol everage the targetb inding and catalytic functions of both constituents. However,t he use of enzymes of nonhuman origin raises the risk of immunogenicity,t hus limiting the dosage and administration frequency of the therapeutic agents.…”
Section: Glutathione Peroxidasementioning
confidence: 99%
“…Camelid immunization has been exploited to generate domains that bind preferentially within enzyme active sites (De Genst et al, 2006; Li et al, 2012), a specificity rarely found among conventional Ig. This has enabled development of potent therapeutic enzyme inhibitors that neutralize bacterial toxins and snake venoms (Wesolowski et al, 2009).…”
Section: Discussionmentioning
confidence: 99%